2014
DOI: 10.1002/prp2.69
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of the cannabinoid CB1 receptor allosteric modulator ORG27569 in rats

Abstract: The cannabinoid CB1 receptor system is involved in feeding behaviors and the CB1 receptor antagonist SR141716A is an effective antiobesity drug. However, SR141716A also has serious side effects, which prompted the exploration of alternative strategies to modulate this important drug target. Recently a CB1 receptor allosteric modulating site has been discovered and the allosteric modulating activity of several modulators including ORG27569 has been characterized in vitro. Yet, little is known of the in vivo pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 47 publications
(97 reference statements)
1
36
0
Order By: Relevance
“…22 While we have seen similar negative results in catalepsy and antinociception in rats, Org27569 attenuated the hypothermic effects of CB1 receptor agonists CP55940 and anandamide. 23 Moreover, we also found that 1 resulted in a dose-related attenuation of both cue- and drug-induced reinstatement of cocaine- and methamphetamine-seeking behavior. 24 Finally, 1 showed high pharmacological selectivity against over forty GPCRs including those commonly involved in drug addictions.…”
Section: Introductionsupporting
confidence: 51%
“…22 While we have seen similar negative results in catalepsy and antinociception in rats, Org27569 attenuated the hypothermic effects of CB1 receptor agonists CP55940 and anandamide. 23 Moreover, we also found that 1 resulted in a dose-related attenuation of both cue- and drug-induced reinstatement of cocaine- and methamphetamine-seeking behavior. 24 Finally, 1 showed high pharmacological selectivity against over forty GPCRs including those commonly involved in drug addictions.…”
Section: Introductionsupporting
confidence: 51%
“…Moreover, this compound generally failed to modify the pharmacological effects of CB 1 orthosteric agonists in common rodent models indicative of CB 1 receptor activity (Gamage et al, 2014). Likewise, ORG27569 generally did not perform as a CB1 receptor allosteric modulator in rats (Ding et al, 2014). Although it attenuated both cue-and drug-induced reinstatement of cocaine and methamphetamine-seeking behavior in rats, CB 1 receptor involvement was not determined .…”
Section: Introductionmentioning
confidence: 95%
“…8 In animal behavioral studies, 1 had no effects on agonist-induced antinociception and catalepsy, grooming and scratching behaviors or drug discrimination. 15, 16 However, similar to CB1 antagonists/inverse agonists, 1 has been demonstrated to reduce food intake and to attenuate CP55,940-induced hypothermia in rats, albeit not in mice. 15, 16 Importantly, 1 also attenuated cue- and drug-induced reinstatement of extinguished cocaine- and methamphetamine-seeking behavior, 17 effects that have been previously observed with CB1 antagonists/inverse agonists, SR141716A and AM251 ( 46 ).…”
Section: Introductionmentioning
confidence: 99%
“…15, 16 However, similar to CB1 antagonists/inverse agonists, 1 has been demonstrated to reduce food intake and to attenuate CP55,940-induced hypothermia in rats, albeit not in mice. 15, 16 Importantly, 1 also attenuated cue- and drug-induced reinstatement of extinguished cocaine- and methamphetamine-seeking behavior, 17 effects that have been previously observed with CB1 antagonists/inverse agonists, SR141716A and AM251 ( 46 ). 1821 On the other hand, reports on the in vivo effects of 2 have been confined to only one study, in which it decreased food intake and body weight.…”
Section: Introductionmentioning
confidence: 99%